Use of Gadgets in Biology Classes as a Means of Increasing Students' Motivation - Victoria Gniezdilova (Vasyl Stefanyk Precarpathian National University, 2021)
The article highlights the current problem of motivating students to learn. The use of gadgets in the educational process can positively affect the motivation of students to learn, involve them in creative activities, as well as interest in better and more honest performance of tasks. Since most students are bored at school, it is difficult to involve them in active work in the classroom. The problem of increasing student activity in the classroom is a fairly common and urgent today. It is difficult to imagine a world without modern technology. Laptops, mobile phones, tablets, computers and other gadgets have become good friends for people. They are real colleagues: they help perform many tasks, which normally take a long time to solve. As with any adult, gadgets play a significant role in children's lives. Teenagers and mobile phones are the same inseparable things as teachers and well-prepared notes. Children are increasingly choosing entertainment in front of a monitor, instead of playing outside or walking with family. Social networks, well-thought-out computer games, take the first place among youth hobbies. That is why the important task facing teachers is to arouse interest in learning, to motivate students. And here ICT are simply irreplaceable: they are the chain that connects the interests of teachers and students. You just need to learn to creatively use children's hobbies with gadgets. Our research has shown how students' attitudes towards biology lessons and their motivation to learn have changed after using the online lab on the Go-Lab platform, the Kahoot application, and QR-codes.